2017
DOI: 10.1108/meq-12-2016-0093
|View full text |Cite
|
Sign up to set email alerts
|

Green chicken purchase behavior: the moderating role of price transparency

Abstract: Purpose Developing green consumption, organic and green meat and poultry consumption have been increased recently. The purpose of this paper is to investigate the effect of food’s sensory characteristics (e.g. organic food beliefs) and non-food factors (e.g. price transparency) on consumers’ green purchase behavior. So, according to the moderating role of price transparency, affecting factors on green chicken purchase intention and behavior are examined. Design/methodology/approach Evaluating the model, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 54 publications
2
36
0
5
Order By: Relevance
“…The moderating effect of price sensitivity between green purchase intention and green purchase behavior was statistically confirmed (H6). These results are consistent with those of Minbashrazgah et al (2017) who stated that the consumers who are less sensitive towards premium price of green products are more likely to purchase them.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The moderating effect of price sensitivity between green purchase intention and green purchase behavior was statistically confirmed (H6). These results are consistent with those of Minbashrazgah et al (2017) who stated that the consumers who are less sensitive towards premium price of green products are more likely to purchase them.…”
Section: Discussionsupporting
confidence: 92%
“…These theories have shown their relevance in different context. Particularly, for green consumption, authors also confirmed the strong relationship between purchase intention and behavior (Ajzen and Fishbein, 2005;Minbashrazgah et al, 2017;Lai and Cheng, 2016;Liobikiene et al 2017). In the same vein, Kanchanapibul et al (2014) stated that the green purchase intention, as consumer's tendency to buying a product because of environmental and human health reasons, often directly drives the buying behavior.…”
Section: Consumers' Green Purchase Intention and Behaviormentioning
confidence: 85%
See 1 more Smart Citation
“…In other words, our study helps to close that knowledge gap. Third, it provides the first empirical evidence regarding the ways in which environmental responsibility mediates the effects of horizontally individualistic and vertically collectivistic cultural values on various green consumption constructs (Minbashrazgah, Maleki, and Torabi 2017). The fourth contribution of this study is managerial.…”
Section: Introductionmentioning
confidence: 89%
“…The consequence of perceived quality and confidence in organic private label on purchase intentions is somewhat moderated by perceived value (62). The above studies provide evidence that organic food quality is demonstrated by green, health, and hedonic upsides (63); that inexpensive and abundant products should not affect healthfulness, the ecosystem, and consuming quality (64); that the market is regulated by the perceived upsides of chemical-free over conventionally cultivated food (57); that altruistic value notably influences biosphere values, which subsequently arouse disposition to spend more on an environmentally friendly menu through pro-environmental attitude (65); and that degree of confidence, consumer's additive-free food beliefs, and perceived green accountability favorably affects organic purchase intention (66). The conclusion drawn from these analyses is that organic consumers mainly purchase environmentally friendly products as they think they are healthier and full of nutrients because of the lack of harmful substances (67), as chemical pesticides and synthetic fertilizers are not employed in organic agriculture.…”
Section: Discussionmentioning
confidence: 99%